The martyrs of Japan: publication history and Catholic missions in the Spanish World (Spain, New Spain, and the Philippines, 1597-1700) - Roldán-Figueroa, Rady (Studies in the history of Christian traditions, 2021)
Background : Catholic missions in Japan -- Japano-martyrology as religious literature -- The production and circulation of martyrological and near-martyrological books, 1598-1700 -- Authors and their institutional contexts -- Publishers, missionaries, and publication portfolios : the dissemination of Japano-martyrology in Southern Europe -- The martyrs of Japan, exemplarity, and post-tridentine spirituality and missions in Luis de Guzmán's Historia de las misiones -- Excursus : how and when was Guzmán's Historia de las misiones "reclassified" from history of missions to travel literature -- Father Luis Piñero, S.J., the tridentine economy of relics, and the defense of the Jesuit missionary enterprise in Tokugawa Japan -- From Nagasaki to Puebla de los Ángeles : Baltasar de Medina (1634-1697) and his martyrology of St. Felipe de Jesús (1572-1597) as an instance of translocal Catholic literary culture.